2020
DOI: 10.3389/fchem.2020.564021
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Assembled Structures for Delivery of Bioactive Compounds and Their Potential in Functional Foods

Abstract: Consumers are demanding more natural, healthy, and high-quality products. The addition of health-promoting substances, such as bioactive compounds, to foods can boost their therapeutic effect. However, the incorporation of bioactive substances into food products involves several technological challenges. They may have low solubility in water or poor stability in the food environment and/or during digestion, resulting in a loss of their therapeutic properties. Over recent years, the encapsulation of bioactive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 190 publications
0
19
0
Order By: Relevance
“…33 Natural products, such as vitamin D, curcumin, naringenin, resveratrol and omega-3 fatty acids, can be well encapsulated inside casein nanomicelles. 34 Theoretically, these nanocomposites or nanoparticles need to be evaluated for safety as food, since the nanoparticles were majorly prepared with sodium caseins. The present study may be valuable for the understanding of the safety of the nutrients encapsulated inside casein nanomicelles.…”
Section: Discussionmentioning
confidence: 99%
“…33 Natural products, such as vitamin D, curcumin, naringenin, resveratrol and omega-3 fatty acids, can be well encapsulated inside casein nanomicelles. 34 Theoretically, these nanocomposites or nanoparticles need to be evaluated for safety as food, since the nanoparticles were majorly prepared with sodium caseins. The present study may be valuable for the understanding of the safety of the nutrients encapsulated inside casein nanomicelles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, milk PL liposomes were more stable than their soy counterparts at various storage and processing temperatures, including changes in pH conditions . The MFGM-derived phospholipids can potentially encapsulate hydrophobic and hydrophilic bioactive molecules . Recently, the MFGM glycoproteins (MUC1) have been preferred for encapsulating LAB .…”
Section: Relationship Of Mfgm With Host–microbe and Brain–gut Microbi...mentioning
confidence: 99%
“…Khor et al showed that the main constituent of papaya leaf extract is flavonoid 52 , where this compound is the main phytochemical component in several types of herbal galactagogues such as Moringa and Foenicullum. Avecedo-Fani et al stated that the structure of casein micelles can be "assembled" with the addition of quercetin, based on the LCMS/MS analysis, quercetin is one of the flavonoid compounds found in Carica papaya leaf in large amount (unpublished data), so the administration of Carica papaya leaf extract can indirectly involve in increasing β-casein levels 53 .…”
Section: Pharmaceutical Sciences Asiamentioning
confidence: 99%